Lean mean thirteen [compact disc, unabridged] - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2007)
Trenton, New Jersey, bounty hunter Stephanie Plum, along with her offbeat family and associates, embarks on her thirteenth perilous adventure.